Implementasi Sistem Kesejahteraan Skandinavia: Studi Perbandingan dan Potensinya di Indonesia - Bakhri, Zorya Kanoubie Attar; Zakwan, Muhammad Faiz; Putra, Sultan Novaliyana; Prama, Raihan Hadi; Pasha, Muhammad Haidar (CV Widina Media Utama, 2024)
Scandinavian countries are renowned for their robust welfare systems, high-quality education, and universal healthcare services, which can serve as models for other nations, including Indonesia. This article examines the potential implementation of the Scandinavian welfare state model in Indonesia by analyzing the current social and economic conditions and formulating practical recommendations for policymakers. Although Indonesia has a strong legal foundation for social welfare, challenges such as limited financial capacity, political issues, and the gap between legislation and implementation pose significant barriers. This study suggests that with appropriate adaptation and innovation, along with active community participation, Indonesia can adopt successful elements of the Scandinavian welfare system to enhance its citizens' quality of life, reduce social and economic disparities, and strengthen social protection.ABSTRAKNegara-negara Skandinavia dikenal dengan sistem kesejahteraan yang kuat, pendidikan berkualitas tinggi, dan layanan kesehatan universal yang dapat dijadikan model bagi negara lain, termasuk Indonesia. Artikel ini mengkaji potensi implementasi model negara kesejahteraan Skandinavia di Indonesia dengan menganalisis kondisi sosial dan ekonomi saat ini serta merumuskan rekomendasi praktis bagi pembuat kebijakan. Meskipun Indonesia memiliki dasar hukum yang kuat untuk kesejahteraan sosial, tantangan seperti kapasitas finansial yang terbatas, masalah politik, dan kesenjangan antara hukum dan pelaksanaannya menjadi hambatan utama. Penelitian ini menunjukkan bahwa dengan adaptasi dan inovasi yang tepat, serta partisipasi aktif masyarakat, Indonesia dapat mengadopsi elemen-elemen sukses dari sistem kesejahteraan Skandinavia untuk meningkatkan kualitas hidup warganya, mengurangi kesenjangan sosial dan ekonomi, serta memperkuat perlindungan sosial.